Cannabidiol in the context of sleeping disorders-induced oxidative stress - Jîtcă George; Ősz Bianca Eugenia; Rusz Carmen Maria; Pușcaș Amalia; Tero-Vescan Amelia; Bătrînu Mădălina Georgiana; Ștefănescu Ruxandra Emilia (Acta Marisiensis - Seria Medica, 2022)
Sleep disorders can be the result of psychiatric or neurological conditions, such as post-traumatic stress disorders, depression, anxiety, Alzheimer’s disease, Parkinson’s disease. At the same time, changes in sleep, known as sleep disorders, are closely related to various metabolic dysfunctions, which in turn are the result of the generation of reactive oxygen species, or otherwise known as oxidative stress. For this reason, cannabinoid derivatives are increasingly used for this purpose. Among the most used are delta-9 tetrahydrocannabinol (THC) and cannabidiol (CBD). These agents interact with the endogenous endocannabinoid system, either by direct action on specific receptors, or by increasing the availability of endocannabinoids, modifying particular mental states (anxiety, depression). The results of the studies specified in this article provide promising evidence regarding the positive effects of CBD, which extend beyond the scope of sleep disorders, with possible applications also in the case of the accumulation of reactive oxygen species.